2019
DOI: 10.1111/jocd.12893
|View full text |Cite
|
Sign up to set email alerts
|

Topical application and oral supplementation of peptides in the improvement of skin viscoelasticity and density

Abstract: Summary Background The combination of oral supplementation and topical formulations to the improvement of skin conditions has been proposed as an innovative approach to obtain effective treatments. However, studies comparing the effectiveness of each type of treatments are still in lack. This way, the objective of this work was to evaluate the clinical efficacy of a dermocosmetic formulation with di‐ and tripeptides, as well the effects of an oral supplementation based on hydrolyzed collagen through biophysica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 14 publications
0
27
0
Order By: Relevance
“…A study of sixty healthy female subjects, aged between 40 and 50 years, after 28 days of oral supplementation showed that this acted on skin elasticity and presented a more pronounced effect on dermis echogenicity, reducing skin pores, improving hydration, texture, elasticity, and firmness of the skin. The oral supplementation product was composed of HC with a mix of vitamins A, C, E, and zinc [126]. HC from tilapia fish scale ( Oreochromis mosambicus ) in the form of 20 mL beverage (Nitta Gelatin Inc ® ., India) was consumed by healthy women aged 30–60 years over 12 weeks, after this time the result was enhanced facial skin moisture [127].…”
Section: Hydrolyzed Collagen: Sources and Applicationsmentioning
confidence: 99%
“…A study of sixty healthy female subjects, aged between 40 and 50 years, after 28 days of oral supplementation showed that this acted on skin elasticity and presented a more pronounced effect on dermis echogenicity, reducing skin pores, improving hydration, texture, elasticity, and firmness of the skin. The oral supplementation product was composed of HC with a mix of vitamins A, C, E, and zinc [126]. HC from tilapia fish scale ( Oreochromis mosambicus ) in the form of 20 mL beverage (Nitta Gelatin Inc ® ., India) was consumed by healthy women aged 30–60 years over 12 weeks, after this time the result was enhanced facial skin moisture [127].…”
Section: Hydrolyzed Collagen: Sources and Applicationsmentioning
confidence: 99%
“…Enzymatic hydrolysis was selected for recovering these by-products with high value-added. The moisturizing properties of hydrolyzed collagen in deeper levels of the skin are very high and may give a very good effect on the looks of the skin [ 72 , 73 , 74 ]. In its hydrolyzed form, collagen is a widely known cosmetic component with antioxidant properties [ 72 ].…”
Section: Hydrolyzed Collagen For Cosmetic Purposesmentioning
confidence: 99%
“…Hydrolyzed collagen acts as a natural humectant with an excellent potential of becoming a harmless and useful biomaterial. It has been shown that supplementation and topical application of hydrolyzed proteins can be considered complementary in the improvement of general skin condition, participating in different mechanisms [ 73 ]. The review of sources and application of hydrolyzed collagen has been performed by León-López et al [ 75 ].…”
Section: Hydrolyzed Collagen For Cosmetic Purposesmentioning
confidence: 99%
“…Innovative studies have been carried out with the combination of topical application of peptides extracted from rice and oral supplementation of HC mixed with vitamin A, C, D, and Zinc. This study was developed in 60 healthy female subjects by applying biophysical and skin imaging techniques [128]. The levels of hydration at deeper layers of the epidermis were improved after one month by the topic application of cosmetic formulation with peptides.…”
Section: Combination Of Both Topical and Oral Intakementioning
confidence: 99%